Gender-affirming hormone therapy: effects on cardiovascular risk and vascular function - Kirsty A McGinley; Angela K Lucas-Herald; Paul Connelly; Christian Delles (Endocrine Connections, 2025)
Background: Gender-affirming hormone therapy (GAHT) is used in individuals with gender identity dysphoria to align their secondary sexual characteristics with their affirmed gender. We conducted a systematic review of the literature to explore the mechanisms regarding the effects of GAHT on the vasculature. Methods: A literature search using PubMed, Embase, Scopus and LILACS was performed using search terms for GAHT, cardiovascular disease (CVD) risk and transgender. Studies were screened by two independent reviewers. Comparison to a cohort of transgender individuals naive or prior to GAHT or a cisgender population was required. Quality assessment was done using the relevant Critical Appraisal Skills Programme checklists. Results: Out of 2,564 potentially eligible studies, 69 studies met the inclusion criteria. Studies provided evidence of beneficial changes in CVD risk profile, including reduced haemoglobin and pro-inflammatory markers, and atheroprotective changes in lipids in transgender women. In transgender men, there was evidence of negative changes in CVD risk profile, including atherogenic changes in lipids and increased haemoglobin, arterial stiffness and pro-inflammatory markers. Conclusions: There is a paucity of research across non-traditional measures of CVD risk, which in combination with heterogeneous study design, loss of follow-up, low sample sizes and lack of diversity in age and ethnicity requires the results to be interpreted with caution. More evidence is required to elucidate the mechanisms behind the increased risk of CVD in the transgender population and determine whether GAHT is a contributing factor.